2008
DOI: 10.1016/j.tet.2008.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of a heterocyclic ansa pyrrole amino acid

Abstract: International audienceWe report a synthetic route to ansa pyrrole amino acids via olefin ring-closing metathesis of diene precursors in the presence of Grubbs I catalyst. The dienes were prepared by Grignard addition to pyrrole sulfinyl imines. The success of the macrocyclic ring closure depends on the dienes structure and only in the case of the 13-membered compound 28 sufficient material could be isolated by preparative HPLC separation to investigate its structure spectroscopically. As also rationalized by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…Noteworthy, the reaction occurred smoothly (CH 2 Cl 2 , 60 h, 40 °C), and its completion was reached provided that 12 mol % of Grubbs II catalyst was used in three subsequent additions (3 × 4 mol %) separated by periods of 20 h. This suggested that the ruthenium species was deactivated in the reaction medium, probably by its coordination to the N-tert -butylsulfinyl moiety, as previously reported for the Hoveyda−Blechert catalyst in the cross-metathesis of N-tert -butylsulfinyl homoallylamines with methyl vinyl ketone . The same phenomenon was also observed by us and others in ring-closing metathesis involving similar substrates. , Under these conditions, compound 5 was therefore isolated in 72% overall yield (three steps from 3 ) after silica gel chromatography. One minor product arising from cross-metathesis of the alkene with the minor isomer of 4 (itself obtained during the addition step) was easily separated and isolated by flash chromatography in 7% yield.…”
Section: Resultssupporting
confidence: 85%
“…Noteworthy, the reaction occurred smoothly (CH 2 Cl 2 , 60 h, 40 °C), and its completion was reached provided that 12 mol % of Grubbs II catalyst was used in three subsequent additions (3 × 4 mol %) separated by periods of 20 h. This suggested that the ruthenium species was deactivated in the reaction medium, probably by its coordination to the N-tert -butylsulfinyl moiety, as previously reported for the Hoveyda−Blechert catalyst in the cross-metathesis of N-tert -butylsulfinyl homoallylamines with methyl vinyl ketone . The same phenomenon was also observed by us and others in ring-closing metathesis involving similar substrates. , Under these conditions, compound 5 was therefore isolated in 72% overall yield (three steps from 3 ) after silica gel chromatography. One minor product arising from cross-metathesis of the alkene with the minor isomer of 4 (itself obtained during the addition step) was easily separated and isolated by flash chromatography in 7% yield.…”
Section: Resultssupporting
confidence: 85%
“…Immediately after the contact of water and organic phase, interfacial reaction initiates, which results in the formation of a solid thin film insoluble in any phase at the aqueous–organic interface. The formed solid thin film possesses a huge surface energy per volume owing to its large surface area-to-volume ratio, , and thus is thermodynamically unstable. , To minimize the surface free energy, some regularly distributed pinhole defects will be formed on the film. , This film with regularly distributed pinholes can be called the nascent film (see Figure a). Thus, MEDA molecules together with the aqueous solution can diffuse through the pinhole defects into the organic phase for further reaction, contributing to the production of small drops of the aqueous phase at the organic side of the nascent film .…”
Section: Resultsmentioning
confidence: 99%
“…Many methodologies have been developed for the preparation of nitrogen-containing heterocycles, with the intramolecular nitrogen nucleophilic displacement of a leaving group being one of the most commonly used. On the other hand, one of the most direct and reliable methods for the asymmetric synthesis of amine derivatives is the addition of an organometallic reagent (mainly organomagnesium, organolithium, organozinc and organoindium derivatives) to the CN bond of enantiopure N -sulfinylimines. In this context, N - tert -butylsulfinyl derivatives have found high applicability in synthesis as electrophiles because both enantiomers are accessible in large-scale processes and because the chiral auxiliary is easily removed under acidic conditions .…”
Section: Introductionmentioning
confidence: 99%